IMPLIKASI CYBERATTACK DALAM KONFLIK RUSIA-UKRAINA TERHADAP STRATEGI PERTAHANAN UKRAINA - Rahmah, Kanjeng Ayu Siti; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
More than a hundred countries are developing cyber military capacity to strengthen security even attack other countries. On 2-24, 2022, Russia launched an invasion of Ukraine in every area of warfare including cyberspace. Russian hackers have initiated attacks on many Ukrainian websites since the beginning of the invasion making government web pages and online banking services inaccessible to the public. This research is a descriptive qualitative with data sources coming from Ukrainian government websites, international organizations and related publications. This paper uses a neorealist perspective with the concept of the Global Cybersecurity Agenda at the country level of analysis within the scope of 2016-2022. The changes can be seen from the renewal of Ukraine's defense strategy which also focuses on the realm of cybersecurity, Ukraine established a special institution that works in the realm of cybersecurity and Ukraine formed international cooperation with NATO in building a national cyber defense system. Ukraine already has several frameworks in place related to cybersecurity. In early 2016, the government approved the first Cybersecurity Strategy of Ukraine. It later issued a second version (Strategy 2020), after which both regulations were canceled with the adoption of Presidential Decree No. 447/2021. Keywords: Cyberattack, Cybersecurity, Cyberweapon and Ukraine Defence Strateg